A Comparison of the effects of preterm birth and institutional deprivation on child temperament. (October 2020) - Reyes, Lucia Miranda; Jaekel, Julia; Kreppner, Jana; Wolke, Dieter; Sonuga–Barke, Edmund
Abstract: Both preterm birth and early institutional deprivation are associated with neurodevelopmental impairment—with both shared and distinctive features. To explore shared underlying mechanisms, this study directly compared the effects of these putative risk factors on temperament profiles in six-year-olds: Children born very preterm (<32 weeks gestation) or at very low birthweight (<1500 g) from the Bavarian Longitudinal Study ( n = 299); and children who experienced >6 months of deprivation in Romanian institutions from the English and Romanian Adoptees Study ( n = 101). The former were compared with 311 healthy term born controls and the latter with 52 nondeprived adoptees. At 6 years, temperament was assessed via parent reports across 5 dimensions: effortful control, activity, shyness, emotionality, and sociability. Very preterm/very low birthweight and postinstitutionalized children showed similarly aberrant profiles in terms of lower effortful control, preterm = −0.50, 95% CI [−0.67, −0.33]; postinstitutionalized = −0.48, 95% CI [−0.82, −0.14], compared with their respective controls. Additionally, postinstitutionalized children showed higher activity, whereas very preterm/very low birthweight children showed lower shyness. Preterm birth and early institutionalization are similarly associated with poorer effortful control, which might contribute to long-term vulnerability. More research is needed to examine temperamental processes as common mediators of negative long-term outcomes following early adversity.